Pengembangan LKPD Berbasis Kontekstual pada Materi Ketahanan Pangan Pertanian di Kelas III SD - Firstya Maulidia; Nurul Istiq’faroh; Amanda Frisca Dianaputri (Tumoutou Social Science Journal, 2026)
This study is motivated by the low interest and reading comprehension ability of elementary school students, which is caused by the use of learning materials that are less engaging and not yet connected to students’ real-life contexts. This condition makes it difficult for students to understand the content of reading texts optimally. Therefore, this study aims to develop a contextual-based Student Worksheet (LKPD) that meets the criteria of validity and practicality in teaching reading comprehension. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 27 elementary school students. Data collection techniques included expert validation questionnaires and student response questionnaires to measure the practicality of the product. The results showed that the developed LKPD was categorized as highly valid based on expert judgment and achieved a practicality level of 87.75%, which falls into the “very practical” category. The contextual-based LKPD helps students understand reading materials by linking them to real-life experiences, making the learning process more meaningful and engaging. Thus, the developed LKPD can be used as an alternative teaching material to improve the quality of reading comprehension learning in elementary schools. This study also implies that the development of contextual and practical teaching materials is essential to support students’ active involvement in the learning process.